Undetectable Concentrations of a Food and Drug Administration–approved High‐sensitivity Cardiac Troponin T Assay to Rule Out Acute Myocardial Infarction at Emergency Department Arrival. (11th August 2017) - McRae, Andrew D.; Innes, Grant; Graham, Michelle; Lang, Eddy; Andruchow, James E.; Ji, Yunqi; Vatanpour, Shabnam; Abedin, Tasnima; Yang, Hong; Southern, Danielle A.; Wang, Dongmei; Seiden‐Long, Isolde; et al.
Abstract: Background: The objective of this study was to quantify the sensitivity of very low concentrations of high‐sensitivity cardiac troponin T (hsTnT) at ED arrival for acute myocardial infarction (AMI) in a large cohort of chest pain patients evaluated in real‐world clinical practice. Methods: This retrospective study included consecutive ED patients with suspected cardiac chest pain evaluated in four urban EDs, excluding those with ST‐elevation AMI, cardiac arrest or abnormal kidney function. The primary outcomes were AMI at 7, 30, and 90 days. Secondary outcomes included major adverse cardiac events (MACE; all‐cause mortality, AMI, and revascularization) and the individual MACE components. Test characteristics were calculated for hsTnT values from 3 to 200 ng/L . Results: A total of 7, 130 patients met inclusion criteria. AMI incidences at 7, 30, and 90 days were 5.8, 6.0, and 6.2%. When the hsTnT assay was performed at ED arrival, the limit of blank of the assay (3 ng/L) ruled out 7‐day AMI in 15.5% of patients with 100% sensitivity and negative predictive value (NPV). The limit of detection of the assay (5 ng/L) ruled out AMI in 33.6% of patients with 99.8% sensitivity and 99.95% NPV for 7‐day AMI. The limit of quantification (the Food and Drug Administration [FDA]‐approved cutoff for lower the reportable limit) of 6 ng/L ruled out AMI in 42.2% of patients with 99.8% sensitivity and 99.95% NPV. The sensitivities of the cutoffs of <3, <5, and <6 ng/L for 7‐day MACE were 99.6, 97.4, and 96.6%, respectively. The NPVs of the cutoffs of <3, <5, and <6 ng/L for 7‐day MACE were 99.8, 99.5, and 99.4%, respectively. A secondary analysis was performed in a subgroup of 3, 549 higher‐risk patients who underwent serial troponin testing. In this subgroup, a cutoff of 3 ng/L ruled out 7‐day AMI in 9.6% of patients with 100% sensitivity and NPV, a cutoff of 5 ng/L ruled out 7‐day AMI in 23.3% of patients with 99.7% sensitivity and 99.9% NPV, and a cutoff of 6 ng/L ruled out 7‐day AMI in 29.8% of patients with 99.7 and 99.9% NPV. In the higher‐risk subgroup, the sensitivities of cutoffs of <3, <5, and <6 ng/L for 7‐day MACE were 99.8, 97.4, and 96.6%, respectively. In this higher‐risk subgroup, the NPV of cutoffs of <3, <5, and <6 ng/L for 7‐day MACE were 99.7, 98.5, and 98.4%, respectively. Conclusions: When used in real‐world clinical practice conditions, hsTnT concentrations < 6 ng/L (below the lower reportable limit for an FDA‐approved assay) at the time of ED arrival can rule out AMI with very high sensitivity and NPV. The sensitivity for MACE is unacceptably low, and thus a single‐troponin rule‐out strategy should only be used in the context of a structured risk evaluation.